(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
In the conditions of the strengthening of the European integration processes and prospective membership of Ukraine in the EU, the experience of the member states of the latter in the development of national economies acquires special importance. The purpose of the article is to evaluate the structural and spatial transformation of Poland’s economy after joining the EU from the perspective of experience for Ukraine. The results of the conducted research revealed that Poland is characterized by a significant unevenness of spatial economic development, which was not overcome, but on the contrary - intensified during the period of this country’s membership in the EU. In particular, in 2021, the Masovian Voivodeship accounted for 22.6% (against 17.4% in 2003) of GVA of agriculture, 15.6% (against 14.9%) of industry, 20.6% (against 15.7 %) of construction, 25.7% (against 22.9%) of the service sector. In 4 voivodeships (Wielkopolska, Mazovia, Lower Silesia and Silesia) more than 50% of GVA of Polish industry, construction and services, as well as more than 40% of GVA of agriculture, are produced. During the analyzed period (2003-2021), differences between Polish voivodships in terms of labor productivity in agriculture tended to decrease, but remained very significant, while in industry these differences slightly increased, and in the service sector they were stable and relatively small. At the same time, the structural transformation of the Polish economy took place in the direction of the development of sectors with higher labor productivity, i.e. those that provide a higher level of GVA and its dynamics. It is about the transfer of human capital from agriculture to industry (in particular processing), construction and certain segments of the service sector, primarily financial. However, heterogeneous structural economic transformations in the regions caused the deepening of spatial divergence in the Polish economy. Based on the Polish experience, in order to avoid the "middle income trap", the management of the spatial development of Ukraine’s economy should not be based on the principles of supporting the weak (segments or enterprises) and not even on the selection of leaders, but on the optimization of all promising opportunities of the region/territory.